The precedent in colombian law: The structuring of the concept and its application by the jurisprudence of the Constitutional Court - Marín Santoyo, Manuel Eduardo (Derecho Público Iberoamericano, 2020)
The precedent as a formal source of law, poses a problem to the legal system provided by the Colombian Constitution of 1991, since the constituent faithful to the European Roman or continental legal tradition, kept as the main source of the law, statuting the jurisprudence as a Secondary source. However, through its judgments the Constitutional Court has cemented the obligatory nature of the precedent for judges, so an analysis of the figure, its concept and value in Colombian law must be carried out.